Blockchain Integration in Fintech: A Framework for Secure and Transparent Digital Transactions - Surya Guntur; Surya Wisada Dachi; Willy Yusnandar (Ilmu Bersama Center, 2026)
The financial technology (fintech) industry has grown rapidly in recent years, driven by the growing demand for fast, secure, and transparent digital transactions. However, data security and transaction transparency remain key challenges that must be addressed. Blockchain technology has emerged as an innovative solution by providing a decentralized system that can enhance security and transparency within the fintech ecosystem. This study aims to analyze the benefits, challenges, and factors influencing blockchain adoption in the fintech industry. The research methodology uses a qualitative approach with literature analysis from relevant national and international journals published over the past three years. The results indicate that blockchain implementation can reduce the risk of fraud, increase transaction efficiency, and strengthen consumer trust through greater transparency. However, blockchain adoption faces various barriers, including high implementation costs, a lack of clear industry standards, limited infrastructure, and the need for comprehensive regulations. Furthermore, increased awareness and education among industry players are needed to encourage broader blockchain adoption. This study provides strategic recommendations for fintech industry players and policymakers, including the need for regulatory development, infrastructure investment, and human resource training. Thus, these findings are expected to contribute to the development of academic literature as well as provide practical guidance for optimizing the application of blockchain in improving security and transparency in the financial sector.